Momentum in Low Carbon and Fossil Fuel Free Equity Investing - Gurrib, Ikhlaas (International Journal of Energy Economics and Policy, 2023)
The Conference of the Parties to the United Nations Framework Convention on Climate Change (COP27) reiterated that climate change remains a critical issue for humanity. Especially, it stressed on the need to encourage a clean energy mix, including renewable and low-emission energies, as part of the continuing transition toward a cleaner and sustainable energy. Using daily indices data covering the period 1st January 2017 to 28th February 2023, this paper studies the performance of 2 family classes among sustainability indices, namely, low carbon and fossil fuel free indices. Specifically, this study sheds further light by assessing the performance of trading strategies which are based on the momentum of low carbon and fossil-fuel free based indices. The performance is based on a thorough analysis of the Relative Strength Index (RSI) and is captured through the Sharpe and Sharpe per trade measures. We decompose the analysis into pre and post COVID-19 to provide some insights how these sustainable energy investments were impacted by the coronavirus pandemic. Findings support an adjusted overbought/oversold RSI 75(25) model resulted in less false signals than the traditional 70 (30) model. Relative to the post COVID-19 period, all selected equity indices performed poorly in the pre- COVID-19 period, with negative returns, except for the MSCI World Low Carbon Leaders and the SPDR MSCI Emerging Markets Fossil Fuel Free equity indices. Comparatively, in the post COVID-19 period, all indices witnessed superior return performance, with also increased risk levels. SPDR MSCI Emerging Markets Fossil Fuel Free index ranked first, even after adjusting for number of trades. Investments post COVID-19 early impact period performed better than a naive buy-and-hold strategy for greener investments like low carbon and fossil fuel free equity indices.